Clinicopathological Overview of Adenoid Cystic Carcinoma of the Salivary Glands at Dr. Hasan Sadikin General Hospital, Bandung, in 2019–2023 - Rakhmiana; Hermin Aminah Usman; Birgitta Maria Dewayani (Global Medical & Health Communication (GMHC), 2025)
Adenoid cystic carcinoma (AdCC) is a rare malignant tumor of the salivary glands, accounting for approximately 1% of head and neck malignancies. This study aims to describe the clinicopathological characteristics of AdCC at Dr. Hasan Sadikin General Hospital from 2019 to 2023. It is a retrospective descriptive study involving 60 AdCC patients diagnosed based on histopathological examination at Dr. Hasan Sadikin General Hospital. Age, gender, primary tumor location, perineural invasion status, distant metastasis, tumor stage, tumor grade, and residual mass were analyzed using SPSS version 26 software. Of the 60 patients, 57% were female, with a mean age of 52 years. AdCC occurred more frequently in the minor salivary glands (79%). Most cases were diagnosed at an advanced stage (38%) and were classified as grade I. Perineural invasion was rare (12%). Distant metastasis occurred in 22% of patients, and residual mass was found in 38% of cases. It may be attributed to the fact that most samples in this study involved minor salivary glands, where the complex anatomical location increases the difficulty of treatment planning and makes surgical approaches to advanced-stage tumors in this area more complicated. In conclusion, most cases of AdCC at Dr. Hasan Sadikin General Hospital from 2019 to 2023 occurred in female patients, with a mean age of 52 years. The tumors predominantly originated from minor salivary glands, were classified as grade I, and were mainly diagnosed at an advanced stage with a high rate of residual mass.